ETR Development and Analysis: Case from the Czech Republic - Jan Svitlík (European Financial and Accounting Journal, 2015)
The paper investigates the effective corporate tax rate (ETR) in the Czech Republic from 2003 to 2013 from the point of both time-series and cross-sectional analysis. We exploit the access to Bureau van Dijk, Amadeus database to get broad data sample from financial statements. Thus, micro backward-looking approach was applied in the paper. We find clear downward trend in the ETR during the given period and statistically significant correlation between the ETR and statutory corporate tax rate (STR). We also undertake analysis of geographical regions using ZIP codes of the companies and analysis of economic sectors according to NACE of the sample firms. Main finding of the cross-sectional analysis is the highest ETR in the region of Prague (capital).
Keywords: H25; M41; 650; Cross-sectional analysis; Effective corporate tax rate; Statutory corporate tax rate; the Czech Republic; Time-series analysis